Forecasting Freight on Board for Gonggong Export in Batam Using Markov Chain - Anggraeni, Andini Setyo; Jabnabillah, Faradiba; Reza, Widya; Cahya Wati, Dia (Jurnal Pijar Mipa, 2024)
As an archipelagic country, Indonesia has great potential in the fisheries sector. As a free trade zone, Batam is important in exporting fishery products. One of the fishery export products in Batam City is gonggong snails. It is a favorite seafood item in Riau Islands Province and has high economic value. However, previous studies focused more on the content of gonggong snails and their industrial feasibility; there has been no specific research on the analysis of gonggong snail exports in Batam City, even though gonggong snails are one of Batam City's export products. In this research, we will forecast the freight on board (FoB) value for gonggong exports in Batam City using a discrete-time Markov chain with two states: above and below the moving average. There are several types of moving averages, including simple moving averages and weighted moving averages. An initial analysis will determine the moving averages' type and duration following the Gonggong export FOB data in Batam. The data used is the Gonggong export FoB data for Batam City from January 2020 to November 2023. Based on this data, the transition probability matrix will be calculated based on the number of export transitions below and above the Weighted Moving Average 6 (WMA 6) value. Limiting probability from the Markov chain will be used to predict the long-term FOB value of fishery product exports up to steady-state conditions. It was found that steady-state conditions would be reached after 17 months, with a probability of FOB exports below WMA6 of 55.06% and FOB exports above WMA6 of 44.94%.